2018
DOI: 10.1073/pnas.1803147115
|View full text |Cite
|
Sign up to set email alerts
|

Elastic coupling power stroke mechanism of the F 1 -ATPase molecular motor

Abstract: The angular velocity profile of the 120° F-ATPase power stroke was resolved as a function of temperature from 16.3 to 44.6 °C using a Δμ = -31.25 at a time resolution of 10 μs. Angular velocities during the first 60° of the power stroke (phase 1) varied inversely with temperature, resulting in negative activation energies with a parabolic dependence. This is direct evidence that phase 1 rotation derives from elastic energy (spring constant, κ = 50·rad). Phase 2 of the power stroke had an enthalpic component in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 71 publications
8
71
0
Order By: Relevance
“…For the intermediate, we postulated a state containing both the incoming ATP and outgoing ADP, similar to the state postulated by Walker et al (25) in which all 3 β subunits are occupied by nucleotides. Alternatively, sequential kinetics for the ATP binding/ADP release was suggested (3,26,27), but a kinetic intermediate was previously undetected. Its ∼10-µs lifetime suggests a microsecond timescale for the lifetime of the proposed intermediate state.…”
Section: Discussionmentioning
confidence: 99%
“…For the intermediate, we postulated a state containing both the incoming ATP and outgoing ADP, similar to the state postulated by Walker et al (25) in which all 3 β subunits are occupied by nucleotides. Alternatively, sequential kinetics for the ATP binding/ADP release was suggested (3,26,27), but a kinetic intermediate was previously undetected. Its ∼10-µs lifetime suggests a microsecond timescale for the lifetime of the proposed intermediate state.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest energy is stored by coiling of the g-subunit two-helix bundle (10); others propose that energy is stored at the 'foot', where g and e are attached to the c-ring (9). Recent cryo-EM studies resolving rotary states of mitochondrial (11), bacterial (12) and chloroplast (13) ATP synthase have all found that the central stalk rotates as a rigid body.…”
mentioning
confidence: 99%
“…The resulting change in contacts is likely to play an important role, as suggested in our previous publication (23). Recent simultaneous single-molecule fluorescence resonance energy transfer (FRET) and rotation measurements (26) support this picture of the rotation cycle, as does the paper by Martin et al (19). In human F 1 -ATPase, on the other hand, it has recently been shown that the rotation takes place in 3 substeps: 0°→ 65°during ATP binding/ADP release, 65°→ 90°with P i release, and 90°→ 120°with ATP hydrolysis (28).…”
mentioning
confidence: 52%
“…This result was subsequently refined to show that the rotation occurs in 40°and 80°substeps (11)(12)(13). [In this work, we use the 40°and 80°notation following Adachi et al (12), although the choice is somewhat arbitrary and other papers use other values (11,(14)(15)(16)(17)(18)(19).] Through these studies, as well as others (20,21), in conjunction with simulations (16,(22)(23)(24), a detailed molecular description of each of the 2 substeps in the γ-subunit rotation cycle was established ( Fig.…”
mentioning
confidence: 99%